I09 Antibodies inhibit cell to cell transmission of mutant HTT. (September 2018) - Bartl, Stefan; Oueslati, Abid; Southwell, Amber L; Parth, Michela; Salhat, Nina; Siddu, Alberto; Burkert, Markus; Pankevych, Halyna; David, Linda; Villanueva, Erika B; Xie, Yuanyun; Cengio, Louisa Dal; et al.
Abstract : The toxic functions of the mutant Huntingtin protein (mutHTT) were studied extensively and in addition to neuronal based symptoms, also peripheral changes upon mutHTT expression were described. An important finding in Huntington's disease (HD) research from the last years is the discovery of extracellular mutHTT and evidence of cell to cell spreading of the mutant protein. This offers new opportunities for targeting mutHTT by antibodies or target-specific vaccines. Recent publications revealed that mutHTT protein was largely present in a free, non-encapsulated form in the extracellular compartment thereby making it accessible by antibodies. We previously demonstrated peripheral target engagement in actively and passively vaccinated YAC128 mice. In these experiments, mutHTT lowering was accompanied by motor improvement in rotarod assays. We sought to generate an in vitro model for testing the molecular mode of action of newly developed mutHTT targeting antibodies and vaccines. Lead antibody C6–17 was capable of depleting mutHTT and blocking intercellular mutHTT transmission, thereby interfering with a potentially disease amplifying mechanism. Our work sets the ground for the development of new antibody-based therapeutics targeting extracellular HD. It is expected that, besides mutHTT depletion, systemic antibody-based targeting will provide inhibition of mutHTT spreading and intercellular transmission. We understand our systemic approach as an addition to forthcoming tissue-specific mutHTT lowering approaches.